SOCIAL CRITICISM IN YUSUF IDRIS' SHORT STORY 'ANA SULTANU QANUNI AL-WUJUDI' - Najma Tanzila; Eva Farhah (UIN Raden Mas Said Surakarta, 2025)
Social criticism in literary works functions as a medium for authors to highlight various societal issues, particularly deviations within social reality. The short story Anā Sulṭānu Qānūni al-Wujūdi by Yusuf Idris exemplifies this by presenting social criticism through animal symbolism. This study employs a descriptive-analytical approach consisting of three stages: data collection, data analysis, and conclusion drawing. The findings reveal four forms of social criticism based on Soerjono Soekanto’s classification, namely criticism of youth (apathy and resistance), poverty, bureaucracy, and crime. These forms of criticism are expressed through the figure of a lion in the circus arena, interpreted as a symbol of various social issues within society.